2020
DOI: 10.1016/j.chempr.2020.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Dinitrogen Electroreduction to Ammonia via Interfacial Polarization Triggered by Single-Atom Protrusions

Abstract: Interfacial polarization is reported as a brand new, efficient, and generalizable strategy to accelerate electrocatalytic reduction of N 2 to ammonia. The polarization is established by using an electric field to polarize N 2 . The electric field is triggered by protrusion-like single atoms anchored on MoS 2 . The interfacial polarization accelerates electron transfer from single atoms to N 2 and thus promotes N 2 reduction. As a result, ammonia synthesis in an electrochemical flow cell proceeds at a high rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
170
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(175 citation statements)
references
References 37 publications
5
170
0
Order By: Relevance
“…[ 11 ] Note that the basal plane of most available 2D electrocatalysts is chemically inert for the N 2 activation, thus is not efficient toward NRR in their pristine form, and the origin of activity and selectivity is primarily associated with their exposed edge sites or defective sites. [ 12 ] Several strategies, such as doping, [ 13 ] interfacial engineering, [ 14 ] and defect modifications, [ 15 ] have been employed to improve the specific activity of materials. However, such tactics typically require strict optimization of the conditions to produce suitable doping or defects (e.g., the solvents, dopants, as well as doping concentrations), and the resulting catalysts suffer from the limited active sites.…”
Section: Introductionmentioning
confidence: 99%
“…[ 11 ] Note that the basal plane of most available 2D electrocatalysts is chemically inert for the N 2 activation, thus is not efficient toward NRR in their pristine form, and the origin of activity and selectivity is primarily associated with their exposed edge sites or defective sites. [ 12 ] Several strategies, such as doping, [ 13 ] interfacial engineering, [ 14 ] and defect modifications, [ 15 ] have been employed to improve the specific activity of materials. However, such tactics typically require strict optimization of the conditions to produce suitable doping or defects (e.g., the solvents, dopants, as well as doping concentrations), and the resulting catalysts suffer from the limited active sites.…”
Section: Introductionmentioning
confidence: 99%
“…Single-atom catalysts (SACs) are expected to have great potential to improve the NRR performance due to the lowest site size,n early 100 %a tomic efficiency and unique lowcoordinated features. [8][9][10][11] Many SACs such as Ru, [12,13] Mo, [14] Fe, [15][16][17] Au, [18] Cu, [19] Y, [20] Ag, [20] and B [21] have been applied for the NRR in aqueous electrolytes.…”
Section: Introductionmentioning
confidence: 99%
“…[35] Compared with the bulk Cu 2 O, the onset potential for N 2 reduction over ultrafine Cu 2 Ow as shifted to positive potentials,a long with am arkedly enhanced current density.R esults suggested that the supported ultrafine Cu 2 Oe nhanced pNRR activity by lowering the energy barrier for N 2 reduction. [36]…”
Section: Methodsmentioning
confidence: 99%